(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to identify the importance of applying the activity-based budgeting method (ABB) in light of the modern business environment and its role in implementing the cost leadership strategy, as the problem faced by the Iraqi economic units in light of the highly competitive business environment, where they suffer from the neglect of the administrations To apply the cost management tools, and to prove the hypothesis of the research, a Wasit Knitting and Textile Factory - Knitting Factory was selected as a sample for the research. Quality while achieving the desires of customers, in addition to the obvious shortcomings of Wasit Textile and Knitting Factory by applying cost management tools.